VARICOSE ULCERS OF THE LOWER LEGS - Dessy Abdullah; Nadia Purnama Dewi; Roland Helmizar; Khomeini Khomeini; Adetetivani Adetetivani (Universitas Pahlawan Tuanku Tambusai, 2023)
Disorders that are often found in the lower extremities are vascular disorders. Varicose veins are very common, especially in women due to venous insufficiency due to poor blood circulation such as reflux and obstructive and can be inherited. The chronic phase of varicose veins can manifest as venous ulcers which is the development of wound below the knee. The lesions appear irregular in shape with clear boundaries, these ulcers can be prevented as early as possible by treating the trigger factor first before referring to the chronic direction. Physical examination is a medical process that must be undertaken when diagnosing a disease. The results are recorded in the medical record which is used to make a diagnosis and plan further treatment. Physical examination will be carried out systematically, starting from head to toe which is carried out in four ways, namely inspection, palpation, auscultation, and percussion. Varicose ulcers are a manifestation of chronic venous insufficiency. Patients with varicose ulcers have a history of varicose veins which, if treated, prevent the occurrence of varicose ulcers.